A Dietary Pattern of Higher Fish, Egg, Milk, Nut, Vegetable and Fruit, and Lower Salt Intake Correlates With the Prevalence and Control of Hypertension. (22nd January 2018) - Yu, Guiquan; Fu, Hang; Huang, Wei; Zhang, Nan; Deng, Dan; Li, Ge; Lei, Han
Abstract: BACKGROUND: The effects of food on the prevalence and control of hypertension are unclear. We aimed to investigate whether a dietary pattern of higher fish, egg, milk, nut, vegetable and fruit consumption, and lower salt intake was associated with hypertension in China. METHODS: A total of 15, 303 subjects were recruited from September 2012 to December 2014. Groups with ( n = 1, 604) and without ( n = 13, 660) hypertension were formed for a case–control study. The hypertensive participants were classified into the controlled blood pressure (BP) subgroup ( n = 397) and the uncontrolled BP subgroup ( n = 1, 207). Data on the average weekly intake of fish, eggs, milk, nuts, vegetables, fruit, and salt in the past year were collected. Higher intake was defined as greater than or equal to median food intake. RESULTS: Higher fish, egg, milk, nut, vegetable, and fruit intake correlated with lower hypertension prevalence, and fish and fruit intake were the strongest associated factors. Meanwhile, higher fruit intake, the highest quartile of egg or milk intake, and the lowest quartile of salt intake correlated with better BP control. Furthermore, the dietary pattern was associated with lower hypertension prevalence (odds ratio [OR]: 0.88, 95% confidence interval [CI]: 0.84–0.92; P < 0.001) and better BP control (OR: 1.11, 95% CI: 1.03–1.21; P = 0.011). However, the dietary pattern did not correlate with BP control after excluding fruit intake. CONCLUSIONS: The dietary pattern correlated with lower hypertension prevalence and better BP control, and its association with BP control might be driven by higher fruit consumption.